Evaluation of Knowledge Attitude and Perception to Benign Prostatic Hyperplasia (BPH) Amongst Public Servants in Federal Capital Territory, Abuja, Nigeria - Lawal, Ibrahim; Danraka, Abubakar; Amlogu, Abraham; Akande, Abdulmujeeb; Ameh, Fidelis Solomon (British Journal of Healthcare and Medical Research, 2023)
Background: Benign prostatic hyperplasia (BPH) is a disease condition in men which affects the prostate gland. There is no consensus about a case definition of benign prostatic hyperplasia (BPH). The incidence of BPH and Prostate cancer has risen in recent decades, with very minimal preventive screening through prostate-specific antigen (PSA) testing. However, prostate cancer mortality rates have remained relatively static over decade. The aim of this study was to determine the knowledge, attitude and perception to BPH and other forms of Prostatic diseases amongst random community-based population of 307 men (age 40 and above). Method: A questionnaire-based descriptive cross-sectional study was carried out amongst male adults above 40 years of age in the Federal Capital Territory (FCT), Abuja, Nigeria. A semi-structured and pre-tested knowledge, attitudes and practices (KAP) questionnaire was administered to the study respondents. Statistical analysis was carried out for frequency, percentages and chi-square measures to test for levels of significance using SPSS. Result: The dominant age group of the respondents was 47 to 49 and majority (38.3 %) had tertiary level of education. Majority of the participants had no knowledge about BPH (67.1 %), Prostate cancer (51.1 %) and PSA screening. Knowledge of its NHIS coverage is at 22.9%. Of the 22.9% that are aware of BPH only an average of 20% are aware of the causes. Cross tabulation of knowledge and attitude of civil servants to BPH, Prostate cancer and PSA test with variables of the demographic data shown significant (p<0.05) correlation. Conclusion: Most of the participants had no knowledge about BPH, Prostate cancer and PSA test. Although some of these association were statistically significant whilst majority were insignificant, more in-depth studies are required to further prove this finding.